Differences of Mean Platelet Volume (MPV) Value Among Clinical Stage of Undifferentiated Type Nasopharyngeal Carcinoma Patient at ORL-HNS Outpatient, Sanglah General Hospital Denpasar (TALENTA PUBLISHER, 2021)
Introduction: Measurement of the mean platelet volume (MPV) is a simple, inexpensive, useful, easy to apply test without additional costs. A high MPV value indicates the presence of large and active platelets in the peripheral blood vessels. Increased MPV value can be a biomarker of nasopharyngeal carcinoma (NPC) malignancies as well as a warning of the risk of thrombosis in malignancy. Objective: To investigate the differences of mean platelet volume (MPV) value among clinical stage of undifferentiated type nasopharyngeal carcinoma (NPC) patient at ORL-HNS outpatient, Sanglah General Hospital Denpasar. Methods: A cross-sectional study with 30 undifferentiated types of NPC patient in ORL-HNS outpatient at Sanglah Hospital Denpasar from January 2017 to December 2019. The sample was selected by systematic random sampling. The analysis used the ANOVA difference test to determine the difference in MPV values among the clinical stage of the undifferentiated type of NPC patient. Results: In this study, the mean age of NPC patients was 50.70 with a standard deviation of 12.55 with the most NPC patients were found to be at the age of more than 50 years. The proportion of NPC patients based on sex was found more in men with 19 patients (63.3%). The mean of MPV value was 12.40 with a standard deviation of 1.27. The highest distribution of undifferentiated types NPC patients among the clinical stage, at stage III and IVA, with 12 patients (40%). The MPV values among clinical stage in patients with undifferentiated type of NPC is significantly different with P= 0.012. Conclusion: In this study there was a significant difference between the MPV value among the clinical stage of the undifferentiated type of NPC in ORL-HNS Outpatient, Sanglah General Hospital with P= 0.012